Acting the part : Photography as theatre - Henry, Karen; Pauli, Lori; Thomas, Ann; Weiss, Marta (Ottawa : National Gallery of Canada Ottawa, 2006)
Adamson, Robert ; Antin, Eleanor ; Barney, Tina ; Bartholomew, Ralph Jr. ; Bayard, Hippolyte ; Bayer, Herbert ; Beveridge, Karl ; Blumenfeld, Erwin ; Cahun, Claude ; Cameron, Julia Margaret ; Carroll, Lewis ; Condé, Carol ; Crewdson, Gregory ; Doisneau, Robert ; Dolejs, Jakub ; Evans, Frederick H. ; Evergon ; Fenton, Roger ; Ferran, Anne ; Fox Talbot, William Henry ; Hannah, Adad ; Hanson, Duane ; Harrison, Gabriel ; Hesler, Alexander ; Hill, David Octavius ; Hiller, Lejaren A. ; Holland Day, Frederick ; Horst, Horst P. ; Hosoe, Eikoh ; Käsebier, Gertrude ; Kells, Harold F. ; Krims, Les ; Madame Yevonde ; Man Ray ; Meatyard, Ralph Eugene ; Michals, Duane ; Morimura, Yasumasa ; Mortensen, William ; Nes, Adi ; Orkin, Ruth ; Outerbridge, Paul ; Price, William Lake ; Prout, Victor Albert ; Qingsong, Wang ; Rau, William H. ; Rejlander, Oscar ; Rey, Guido ; Robinson, Henry Peach ; Sherman, Cindy ; Shonibare, Yinka ; Snow, Michael ; Sussman, Eve ; Thompson, Warren ; Viola, Bill ; Wall, Jeff ; Weegee ; Weems, Carrie Mae ; Weston, Edward ; Zahalka, Anne
Acting the part : Photography as theatre, National Gallery of Canada, Ottawa, 2006-06-16. 2006-10-01
boek